Wheat (Triticum aestivum L.) transformation with Bar gene expression cassette lacking vector backbone sequences - SHI Nong-nong; HE Guang-yuan; LI Ke-xiu; WANG Hui-zhong (浙江大学学报. 农业与生命科学版, 2007)
To explore the transformation efficiency on cultivated wheat with gene expression cassette lacking vector backbone sequences, transformation of wheat cultivars by biolistic bombardment with bar gene expression cassette was proceeded through isolating immature embryos and inflorescences, excising gene cassette, biolistic bombarding, regenerating, PCR amplifying and leaf-painting assaying. 23 independent plantlets from embryogenesis of immature embryos were selected, 18 of which showed the integration of bar gene expression cassette and all appeared the herbicide tolerance. The transformation frequency of genotype Emai 12 (1.55%) is higher than that of Een 1 (0.87%). The two genotypes both presented higher frequencies under 1100 psi bombarded pressure than under 900 psi, Emai 12 reached 3.51% and was higher than the general transformation frequency (0.5%-1.00%) of wheat. Genotypes, explants and bombarded pressures are vital in optimizing the transformation system of gene expression cassette. Transformation of gene expression cassette is proved to be an effective approach in genetic manipulation.